Association of prior infection with chlamydia and cerebrovascular disease - Ulvi, Hizir; Önal, Süleyman; Yoldaş, Tahir; Yi?iter, Remzi; Polat, Nilgün; Müngen, Bülent (Turkish Society of Cerebrovascular Diseases, 2003)
Purpose: Chlamydia pneumoniae is a human respiratory pathogen that causes acute respiratory disease and ?10% of community-acquired pneumonia. The infections are geographically widespread. In addition to respiratory disease, seroepidemiologic studies have shown an association of this organism with atherosclerotic proces and cerebrovascular disease. The role of preceding chlamydial infection as a risk factor for stroke was investigasted. Material and Methods: We studied 68 consecutive patients under 65 years of age with cerebrovascular disease; the mean age was 52.08 ± 5.74 years (yrs) (range 39 yrs to 64 yrs; 28 female and 40 male) and 29 randomly selected age-matched healthy subjects (control); the mean age was 49.76 ± 13.11 years (yrs) (range 41 yrs to 62 yrs; 12 female and 17 male). Specific antibodies to C pneumoniae and C trachomatis in serum were measured by the microimmunofluorescence with the method of Wang and Grayston in all the subjects. Quantitative variables were analyzed with Mann-Whitney test. Results: The mean values of antibodies titers in patients (mean IgG antibodies to C pneumoniae in patients, 1.382 ± 0.256 vs. control, 1.152 ± 0.334 [p=.012], mean IgG antibodies to C trachomatis in patients, 0.043 ± 0. 019 vs control, 0.031 ± 0.015 [p=.026]) were significantly higher compared with the controls. Although the mean IgM antibodies titers to C pneumoniae and C trachomatis are lower and IgA to C pneumoniae higher in patients than the controls, this differences were not found to be significant (mean IgM antibodies to C pneumoniae in patients, 0.502 ± 0.188 vs. control, 0.559 ± 0.149 [p=.087], mean IgM antibodies to C trachomatis in patients, 0.451 ± 0.348 vs. control, 0.683 ± 0.578 [p=.140], mean IgA antibodies to C pneumoniae in patients, 1.008 ± 0.246 vs. control, 0.971 ± 0.237 [p=.563]). Conclusion: We conclude that chronic infection with chlamydiae is associated with an increased risk of cerebrovascular disease and believe that patients who have high values of IgG antibodies titers should be warned for a probable cerebrovascular disease and other risk factors like smoking, alcohol, diet, etc.
Keywords: And risk factors; Atherosclerosis; Cerebrovascular disease; Infection